The Confusion Caused by the Fear of COVID 19 in the Future of Cancer Patients (Bangladesh Journal of Medical Science, 2023)
Objective: The “centrality of events scale” (CES) was formed to determine to what extent this localisation of a traumatic memory is formed. The CES was used in this study to determine how overshadowed the cancer disease was by fear of COVID-19 in cancer patients or how centralised the cognitive trauma was in this patient group.Materials and Methods: In the first paragraph of the short 7-item CES, it was written, “Please think about the most stressful or traumatic event in your life”, then 3 options were given. These alternatives were: A) I am currently being treated here for my disease., B) I am likely to catch COVID-19 and C) Other. After marking one of these options, the subjects were instructed to mark their level of agreement with the 7 items as stated by Berntsen and Rubin, and thus this section was the same as the original questionnaire. To be able to evaluate the questionnaire results taking the disease characteristics into account, a record was made of age, gender, treatment history (chemotherapy and radiotherapy), current treatment (chemotherapy, hoemone therapy, immunotherapy, monoclonal antibodies, tyrosine kinase inhibitors) treatment aim (adjuvant, neoadjuvant, palliative), disease status on presentation (no spread, local, metastatic).The questionnaires were administered to all the cancer patients who presented at the oncology clinic between 1 April and 1 October 2020.Results: This study was conducted to seek an answer to this question, and it was seen that of a total of 523 patients diagnosed with cancer, the vast majority (n:368, 70.4%) saw the most traumatic and stressful event of their life as cancer, with the response to option A on the questionnaire. The possibility of contracting COVID-19 was selected by 83 (15.9%) patients as the most stressful or traumatic event in their life. The option of C was marked by 72 (13.8%) patients. This showed that neither cancer nor fear of coronavirus infection was strong enough to replace the traumatic event experienced and centred in the identity of these 72 patients. These traumas of the patients were analyzed with the mean CES points. The highest points were obtained by those who marked option A, at 3.71, which was statistically significantly higher than the 3.29 points for B and 3.29 points for C (p:0.004).Conclusion: A trauma left in the past actually lives on in the cognitive memory and may even be established at the centre of the self and personal identity. Thus, by modifying the short 7-item CES, developed by Berntsen and Rubin to be an objective, measurable format, the results of this study demonstratated both the extent to which the possibility of contracting COVID-19 has started to be established in cancer patients and the unshakable but declining centrality of cancer in the traumatic past.Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 68-76